Betty before X - Shabazz, Ilyasah; Watson, Renée (Square Fish, 2018)
The granddaughter of Malcolm X tells a fictionalized story from her mother's childhood. Betty Shabazz is a young girl learning first-hand about the real change people can make when they help each other and the power of acceptance and belonging. But when a terrible crime happens in her neighborhood, she learns that things aren't always as clear as she once thought.